MEDB-54. Standard Risk Medulloblastoma treated solely with surgery and chemo-radiation. (3rd June 2022) - Cantor, Evan; Meyer, Ashley; Ogle, Andrea; McHugh, Michele; Beck, Mary; Green, Tammy; Ramachandran, Lakshmi; Dahiya, Sonika; Cluster, Andrew; Brossier, Nicole M; Abdelbaki, Mohamed S; Limbrick, David; et al.
Abstract: INTRODUCTION: Medulloblastoma is the most common malignant brain tumor in children, with 5-year overall survival (OS) ranging from 60%-95% depending on subgroup and risk status. The POG 8631/CCG 923 trial (accrual 1986-1990) found a 63% 5 year OS for patients with local disease after gross total resection treated with radiation at a dose of 23.4 Gy craniospinal radiation and posterior fossa boost to 54 Gy, vs. 80.5% 5-year OS for patients treated as per full ACNS0331 therapy including maintenance chemotherapy. Herein, we describe a long-term survival with standard-risk medulloblastoma who only received surgical resection and radiation therapy. CASE: A 17-year-old male presented with acute onset of hypertension, bradycardia, headache, and blurry vision and was found to have a heterogeneously enhancing posterior fossa mass with mass effect on the fourth ventricle and hydrocephalus on brain MRI. He underwent gross total resection of the tumor and histopathology revealed medulloblastoma with classic and large cell features. Fluorescence in situ hybridization (FISH) was negative for MYC, MYCN amplification, or HER2 gain. Cerebrospinal fluid cytology was negative for neoplastic cells, and spinal MRI did not reveal any drop metastases. The patient initiated therapy per ACNS0331 with craniospinal irradiation posterior fossa boost. He also received weekly vincristine. After completion of radiation therapy, the family declined further chemotherapy despite medical advice. He had no evidence of relapse most recently at 51 months from completion of therapy. Next generation sequencing and methylation testing are currently pending. CONCLUSION: Current efforts aim at optimizing therapy based on molecular subgrouping, to minimize long-term adverse events associated with current therapies. We report a unique case of an adolescent male with an standard-risk medulloblastoma, who achieved remission with only radiotherapy. Further molecular tumor analysis may elucidate the response of the tumor.